PEMBERDAYAAN INDUSTRI RUMAH TANGGA JAJAN BANTEN DI DESA UBUNG KAJA-DENPASAR - I Nyoman Senimantara; Anak Agung Bagus Amlayasa; Ni Putu Riasning (UNHI Press, 2022)
This religious culture is inseparable from the element of beauty and uniqueness of the ceremony (Banten) which is offered every time the ceremony takes place. The main element in every ceremony is the presence of sampyan (decoration of the leaves), fruit, and Banten snacks. It has become a culture in Bali that the offerings made always use snacks as a compliment. There are various types of Banten snacks, such as sun snacks, satuh, kaliadrem, and many more. However, what must be in every offering is snack uli (Jaja Uli) and Begina. IRT Jaja Uli Asanadi's business focuses on Jaja uli and this is an effort to preserve traditional snacks as a complement to the offering element in every yadnya ceremony. During this business, various problems can be identified that befall partners, namely the lack of purchasing power of partners in purchasing equipment resulting in low production activities, partners do not yet have an understanding regarding how to market products, where so far partners are still using the word-of-mouth marketing system. As a result of this PKM activity, partners are given education about how to market products only. Promotional programs through the affixing of business stickers can easily remember the business name and phone number, making it easier to place an order.